Nestin-expressing vascular wall cells drive development of pulmonary hypertension. Issue 3 (23rd December 2015) - Saboor, Farhan; Reckmann, Ansgar N.; Tomczyk, Claudia U.M.; Peters, Dorothea M.; Weissmann, Norbert; Kaschtanow, Andre; Schermuly, Ralph T.; Michurina, Tatyana V.; Enikolopov, Grigori; Müller, Dieter; Mietens, Andrea; Middendorff, Ralf
Nestin, a well-known marker of neuronal stem cells, was recently suggested to characterise stem cell-like progenitors in non-neuronal structures during development and tissue repair. Integrating novel morphological approaches (CLARITY), we investigate whether nestin expression defines the proliferating cell population that essentially drives vascular remodelling during development of pulmonary hypertension. The role of nestin was investigated in lungs of nestin-GFP (green fluorescent protein) mice, models of pulmonary hypertension (rat: monocrotaline, SU5416/hypoxia; mouse: hypoxia), samples from pulmonary hypertension patients and human pulmonary vascular smooth muscle cells (VSMCs). Nestin was solely found in lung vasculature and localised to proliferating VSMCs, but not bronchial smooth muscle cells. Nestin was shown to affect cell number and was significantly enhanced in lungs early during development of pulmonary hypertension, correlating well with increased VSMC proliferation, expression of phosphorylated (activated) platelet-derived growth factor receptor β and downregulation of the smooth muscle cell differentiation marker calponin. At later time points when pulmonary hypertension became clinically evident, nestin expression and proliferation returned to control levels. Increase of nestin-positive VSMCs was also found in human pulmonary hypertension, both in vessel media and neointima. Nestin expression seems to be obligatory for VSMC proliferation, and specifies lung vascular wall cells that drive remodelling and (re-)generation. Our data promise novel diagnostic tools and therapeutic targets for pulmonary hypertension. In lung, nestin is solely found in vascular smooth muscle cells and drives remodelling in pulmonary hypertension http://ow.ly/StPCS